Sanctuary cinema : origins of the Christian film industry - Lindvall, Terry (New York : New York University Press, 2007)
Sanctuary Cinema provides the first history of the origins of the Christian film industry. Focusing on the early days of film during the silent era, it traces the ways in which the Church came to adopt film making as a way of conveying the Christian message to adherents. Surprisingly, rather than separating themselves from Hollywood or the American entertainment culture, early Christian film makers embraced Hollywood cinematic techniques and often populated their films with attractive actors and actresses. But they communicated their sectarian message effectively to believers, and helped to shape subsequent understandings of the Gospel message, which had historically been almost exclusively verbal, not communicated through visual media. -- PUBLISHER'S DESCRIPTION.
The Brazen serpent -- Sanctuary cinema -- Divine shows -- Better films -- Film as religion.
OldControl:muse9780814753231.
Includes bibliographical references (pages 293-296) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Silent films -- United States -- History and criticism; Motion pictures in Christian education; Christian films -- United States -- History and criticism; Motion pictures -- Religious aspects -- Christianity; Films muets -- États-Unis -- Histoire et critique; Cinéma dans la catéchèse.; Films chrétiens -- États-Unis -- Histoire et critique; Cinéma -- Aspect religieux -- Christianisme; PERFORMING ARTS -- Reference; Christian films; Motion pictures in Christian education; Motion pictures -- Religious aspects -- Christianity; Silent films; United States; Stummfilm; Christ; Films; Christendom; Stummfilm -- USA -- Geschichte; Film -- Motiv -- Religion -- USA -- Geschichte; Religion -- Motiv -- Film -- USA -- Geschichte; Christentum -- Filmindustrie -- USA -- Hollywood -- Geschichte -- 1895-1930.; Film -- Motiv (Kunst) -- Christentum -- Geschichte -- 1895-1930.; Christentum -- Motiv (Kunst) -- Film -- USA -- Hollywood -- Geschichte -- 1895-1930.; Hollywood -- Filmindustrie -- Christentum -- USA -- Hollywood -- Geschichte -- 1895-1930.; "Multi-User"; Criticism, interpretation, etc